Musical creativity: Multidisciplinary research in theory and practice - Deliège, Irène; Wiggins, Geraint A. (Hove Psychology Press, 2006)
This collection initiates a resolutely interdisciplinary research dynamic specifically concerning musical creativity. Creativity is one of the most challenging issues currently facing scientific psychology and its study has been relatively rare in the cognitive sciences, especially in artificial intelligence. This book will address the need for a coherent and thorough exploration.Musical Creativity: Multidisciplinary Research in Theory and Practice comprises seven sections, each viewing musical creativity from a different scientific vantage point, from the philosophy of computer modelling, through music education, interpretation, neuroscience, and music therapy, to experimental psychology. Each section contains discussions by eminent international specialists of the issues raised, and the book concludes with a postlude discussing how we can understand creativity in the work of eminent composer, Jonathan Harvey.This unique volume presents an up-to-date snapshot of the scientific study of musical creativity, in conjunction with ESCOM (the European Society for the Cognitive Sciences of Music). Describing many of the different aspects of musical creativity and their study, it will form a useful springboard for further such study in future years, and will be of interest to academics and practitioners in music, psychology, cognitive science, artificial intelligence, neuroscience and other fields concerning the study of human cognition in this most human of behaviours.